ANALYSIS OF THE DEVELOPMENT AND FINANCIAL PERFORMANCE OF PT UNILEVER INDONESIA TBK IN THE LAST FIVE YEARS - Neza Alkhaira; Isna Septia; Junita Munasari; Wulan Dara Sari Arhas; A. Hadi Arifin (Journal of Accounting Research, Utility Finance and Digital Assets, 2024)
The Research This analyze development and performance finances of PT Unilever Indonesia Tbk in five years last . As A company operating in the fast moving consumer goods (FMCG) sector , Unilever is facing change behavior consumers , pressure global economy , as well as impact recovery post-pandemic . Research use method descriptive with approach studies library through report annual report finance , and literature supporters . Research results show that Unilever is capable maintain stability business although profitability experience fluctuations consequence increase cost production . Liquidity company still strong Because efficiency operational and strengthening digital strategy. In overall , Unilever pointed out resilience through strategy adaptation , strength brand , as well as commitment to sustainability .